(untitled) (Vietnam Journal of Agriculture and Environment, 2023)
Asparagus (Asparagus officinalis L.) is known as a valuable vegetable due to its richness in anti- cancer and antioxidant compounds, vitamins, minerals, and high economic efficiency. Asparagus is being expanded in production in Vietnam. Breeding asparagus varieties has not been carried out in Vietnam, so asparagus varieties grown in Vietnam are all imported varieties. The study aimed to choose the best varieties among 12 asparagus varieties imported from the US and Netherlands for production in the Red River Delta, Vietnam. The yield of spears was assessed in the spring and autumn season 2022 using the second-year asparagus in the field of the Field Crops Research Institute, Hai Duong province, Vietnam. The results indicated that Atlas F1 was the variety with the most advantages in both seasons, with a low infection rate of stemblight, large diameter of spears, high dry weight of spears, high yield and yield component, and moderate vitamin C content. In addition, Purple passion was also a special variety with high stability due to its low infection rate, high dry weight, high vitamin C content in both seasons, high sugar accumulation rate in roots, root CHO, and total sugar content in the autumn season 2022, although the yield productivity and yield component were low. The results also showed a positive and significant correlation between asparagus yield productivity and root Brix in both seasons of 2022. The results suggest that the root Brix of asparagus could be the target trait for choosing varieties for production.